Loading behaviour of 900 'UREAD' energy channels - LUPOI, ROCCO (My University, 2008)
Most engineering products are designed to either deliver or withstand a specific maximum force or level of energy. It is important however that the design of a structure or a machine incorporates an external or internal mecha nism to overcome excessive loading, so as to reduce human discomfort and unsafe operations. Material elastic properties are exploited in most energy absorption devices but they have the disadvantage of generating rebound forces, in some cases comparable t o those being absorbed. This paper examines the validity of a new concept which has been implemented into a Universal Re - usable Energy Absorption Device – ‘UREAD’. A passageway made out of intersecting channels of a constant cross - sectional area is con structed inside the device where, upon the application of force, a piece of deformable material is allowed to flow through it. Energy is dissipated through intense shearing at each intersecting channels . Experiments were applied to devices characteri zed by two intersecting channels at 90 ̊ . Passageways of square and circular cross sectional areas in the range of 60 - 100mm 2 were tested using Silicon gum and lead. The results showed a typical pattern of deformation where the load remains almost consta nt after the initiation of plastic deformation through the channels. Material yield strength, billet length, and passage way cross - sectional area appear to be major contributors to the level of absorbed energy. The pattern of deformation under plane s train conditions was investigated by the Finite Element Analysis (FEA), and the predictions showed a yielding process that is dominated by internal shearing zones.
PUBLISHED
Keywords: Finite element analysis; ECAE; Severe plastic deformation; UREAD; Energy absorption